Synthesis, Structure, and Hirshfeld Surface Analysis of tetrakis(N,N’-diethylthiourea)bis(isothiocyanato)nickel - Husni Wahyu Wijaya; Danar; Zainal Abiddin; I Wayan Dasna (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2023)
The complex compound tetrakis(N,N’-diethylthiourea)bis(isothiocyanato)nickel or [Ni(detu)4(NCS)2] (denoted as UMCC-1) has been synthesized by reflux method in two different solvents namely acetone and methanol. This study aims to synthesize, characterize, and analyze the Hirshfeld Surface complex UMCC-1, which was obtained using the reflux method with the mole ratio of NiCl2: detu: KSCN is 1:2:4. Single crystals UMCC-1 in acetone and methanol are dark green in color with melting points of 135-137°C and conductivity of 66.4-84.4 µS. The FTIR absorption band analysis of the two crystals is very similar, ν(C S) detu 590 cm−1 and ν(C≡N) isothiocyanate 2119 cm−1. The refinement of the crystal structure from the single crystal XRD data shows that the two dark green crystals are a molecular type that has a distorted octahedral geometry with the same crystal lattice, monoclinic crystal lattice, P21/c1 space group (no.14), crystal lattice parameter a= 11.112(3) Å, b= 17.249(5) Å, c= 9.647(3) Å, and β= 100.785(10). However, the complex produced in acetone solvent has better refinement quality than methanol concerning %R= 3.27 and %R = 4.55, respectively. The UMCC-1 crystal shows intermolecular hydrogen bonds N-H—S(isothiocyanato) and intramolecular hydrogen bonds N-H—S(detu) with Hirshfeld Surface analysis showing a significant contribution of H—H (69.5%) on crystal packing.